Multi-user virtual reality software development kit for research - 이우현 (The Graduate School, Ajou University, 2024)
Virtual reality (VR) technology is advancing in many fields, such as science, medicine, education, and psychology, moreover, VR applications are becoming diverse. There is also a growing interest in multi-user experiences, where many people synchronize and play together over a network. As a result, various research utilizing multi-user VR is on the rise. We introduced MultiPlayXR, a novel SDK designed to develop multi-user VR applications on the Unity game engine. This SDK aims to address the limitations of existing VR SDKs, particularly their platform dependence and lack of data collection features essential for research experiments. The objectives of MultiPlayXR include ensuring scalability, platform independence, and ease of use for developers, especially those new to multi-user VR. The key features of MultiPlay XR are interaction, data collection, and Immersive experiences. A key component of the research was the development of Ready Player Speak, a multi- user speech training VR application built using MultiPlayXR. This application, running on Meta Quest Pro, served as a proof-of-concept to demonstrate the SDK's feasibility for the development of multi-user VR content for research. The study involved 29 participants (13 females, 16 males), primarily university students from South Korea, who gave a speech in the virtual auditorium and answered questions based on it. Data collection instruments, such as pre-and post-test questionnaires, interviews, and sensors of Meta Quest Pro (facial expressions, eye gaze, and body tracking), were used for comprehensive data acquisition. The results indicated the potential of MultiPlayXR for research purposes, with its design patterns proving effective for the development and maintenance of multi-user VR applications. The feasibility study of Ready Player Speak showed promising outcomes in terms of user experience, presence, and data collection. However, the study also identified limitations, including the need for more cohesive data collection methods, the lack of device independence in the SDK, and areas for refinement in the VR experience. In conclusion, MultiplayXR demonstrated the feasibility of developing multi-user VR applications for research purposes. Its focus on data collection, ease of development, and adaptability to future VR advances make it a promising tool for researchers and developers. Keywords: Virtual reality Software Engineering, Public Speaking, Feasibility Study, Multi-user, Presence, User experience
학위논문(석사)--미디어학과,2024. 2
Keywords: Feasibility Study; Multi-user; Presence; Public Speaking; Software Engineering; User experience; Virtual reality